(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article provides a comprehensive analysis of the impact of green investments—capital allocations based on environmental, social, and governance (ESG) criteria—on the long-term financial stability of companies. The study examines both the positive effects and limiting factors of green investments from the perspectives of operational cost dynamics, access to capital, risk management efficiency, brand equity, and market competitiveness. Taking into account the economic context of Uzbekistan, the financial implications of implementing ESG strategies for national companies are evaluated. In conclusion, when properly implemented, green investments significantly strengthen a company’s financial stability and become a source of competitive advantage.